Developing a Bench-Scale Green Diboration Reaction toward Industrial Application - Farre, Albert; Briggs, Rachel; Pubill-Ulldemolins, Cristina; Bonet, Amadeu (Synthesis, 2017)
We report a new methodology for the organocatalytic diboration reaction using inexpensive, sustainable, nontoxic, commercially available halogen salts. This is an educative manuscript for the transformation of laboratory scale reactions into a sustainable approach of appeal to industry.
Keywords: green chemistry; organocatalysis; boron chemistry; ate complexes